Pedagogical decisions in lesson planning and making use of the planning: Perspective of both experienced and novice teachers - Pratiwi, Dwiyani (UIN Raden Mas Said Surakarta, 2024)
The differences between experienced and novice teachers can be observed in how they plan and implement lesson plans in the classroom. Understanding these strategies can aid teacher education programs in refining their curricula to better develop teachers' competencies. This research explores the perspectives and practices of both experienced and novice teachers regarding lesson planning and its actual use. A qualitative case study was conducted, involving two rounds of interviews with one experienced teacher and two novice teachers. Using qualitative data analysis techniques, the data were categorized into several themes. The findings reveal that all teachers recognize the importance of lesson planning. They unanimously agree that written lesson plans, referred to as lesson plan pro forma, are essential for guiding teaching and fulfilling administrative functions. However, differences emerged in how they planned their lessons, responded to policy changes and regulations, and made pedagogical decisions when addressing critical incidents in the classroom. The experienced teacher demonstrated greater readiness and adaptability to changes in the curriculum, classroom dynamics, students' needs, and school regulations. Conversely, the novice teacher, due to a lack of knowledge and skills in lesson planning, tended to rely on the school-selected workbook as the primary resource for teaching directions. Implications for teacher professional development programs and recommendations for further research are discussed.